7(2p+3)=6p+29

Simple and best practice solution for 7(2p+3)=6p+29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(2p+3)=6p+29 equation:


Simplifying
7(2p + 3) = 6p + 29

Reorder the terms:
7(3 + 2p) = 6p + 29
(3 * 7 + 2p * 7) = 6p + 29
(21 + 14p) = 6p + 29

Reorder the terms:
21 + 14p = 29 + 6p

Solving
21 + 14p = 29 + 6p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-6p' to each side of the equation.
21 + 14p + -6p = 29 + 6p + -6p

Combine like terms: 14p + -6p = 8p
21 + 8p = 29 + 6p + -6p

Combine like terms: 6p + -6p = 0
21 + 8p = 29 + 0
21 + 8p = 29

Add '-21' to each side of the equation.
21 + -21 + 8p = 29 + -21

Combine like terms: 21 + -21 = 0
0 + 8p = 29 + -21
8p = 29 + -21

Combine like terms: 29 + -21 = 8
8p = 8

Divide each side by '8'.
p = 1

Simplifying
p = 1

See similar equations:

| 46+2y=443+y | | 7x-(4x+21)=2-(7x-4) | | 7.5x+8=7x | | 81/9(10-9) | | (3x)(-2xy)(-4xy)= | | -3=-1/2x | | ab=3c-2 | | 3n+35=2n+45 | | Ab=3c+2 | | 9e+4=4+8e | | x-(-3.4)=-4 | | 20-120.5= | | 3x+2+4=0 | | 4=f/ | | 5x(5x-7)=0 | | -1/(3-y) | | 2y=6y-220 | | Y^3-5y^2+6y-30= | | 9X+150-72X=150 | | -3+5(8+6r)=37 | | Z+8+-43+[-12]=20 | | 9/0.4 | | 4x+6-21x=19 | | 42x+15=32x | | y=6=5/2x-4 | | 28y^6-8y^3/4y^3 | | 3x+2-6=4 | | 2+8+-43+[-12]=20 | | |3x-3/9|1 | | 9xy-4x+y= | | 24x+5=42 | | 4y+8=4y+4 |

Equations solver categories